Pemanfaatan Teknologi Informasi Sebagai Media Pembelajaran Guru Dalam Pembelajaran Jarak Jauh Selama Pandemi - Oki Heryanto (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
Distance Learning (PJJ) is a form of social distancing that is carried out so that every student has the right to continue to study during the Covid-19 pandemic. Distance Learning (PJJ) provides higher education services to community groups who cannot attend face-to-face education, and expands access and facilitates higher education services in learning. The learning system carried out by students and teachers through learning media by utilizing information technology. The purpose of this study was to describe the use of information technology as a medium of learning by teachers and to find out the state of technology available in schools as a means of supporting distance learning. This study uses a qualitative descriptive method with a case study approach. Data collection was carried out by studying literature and interviewing four resource persons from state elementary school teachers, junior high schools, and high schools located in the city of Tulungagung, East Java. The collaboration of students, teachers, schools, parents, and the government determines the success of PJJ, especially for the availability of learning support tools and internet access. Teachers adapt and are required to innovate in utilizing technology. There is a change in the use of technology for the sustainability of education in Indonesia.